A Taylorian approach to social imaginaries: the origins of Chile’s democratic culture - Montero, Dario (2015)
The recent wave of social movements in Chile seem to express a profound critique against democracy, as this modern ideal has been interpreted and practiced in this country. In our view, the current legitimation crisis can be explained as a clash of two social imaginaries whose first traces are already visible during early republican life and which together constitute Chile’s political culture. According to this longer-term approach we need to return to the founding period when the nation and the state were built and delve into the origins of the Chilean constitutional tradition. The ‘founding clash’ of political self-interpretations and its outcome, which took place between 1810 and 1833, determined path-dependently the outlook of Chile’s democratic culture as we know it today. Charles Taylor’s imaginaries approach has served as a guide to explore the cultural face of Chile’s political modernity by attending to the unique way in which the North Atlantic modern social imaginary has been re-configured when placed within a pre-modern (colonial) Hispano American social imaginary. Since the early part of the nineteenth century, Chile’s legal and political structures seem to have been justified instrumentally, in accordance with a liberal-atomistic imaginary, combined with an authoritarian element inherited from colonial times. But we also find such liberalism co-existing right from the beginning of the Republic with the presence of a popular-democratic social imaginary –in a way, coextensive to all the Hispano-American peoples. This latter affirms the value of community and citizen participation. Chilean social movements, in particular those of a political-constituent kind, have not challenged liberalism per se but have sought to find a way of realizing popular sovereignty through greater participation and the establishment of what they consider a truly liberal-democratic system. In doing so, they are heirs to that original popular social imaginary, which was violently suppressed and displaced from the political ...